Intervention diversity predicts social rehabilitation indicators at discharge in Therapeutic Communities - Barreto, Kátia Isicawa de Sousa; Madruga, Clarice Sandi; Miguel, André Constantino; Smith, Crystal; Apolinário, Gleuda Simone; Godoy Filho, Guilherme Sabino de; Guirado, Lucas Roncati; Kurlander, Pablo Andres [UNESP]; McPherson, Sterling; Laranjeira, Ronaldo Ramos (Elsevier, 2024)
Introduction: The Therapeutic Community Model narrows the gap in substance use disorder's network of assistance in Brazil by offering residential treatment to socially vulnerable populations. Due to a historical lack of evidence-based approaches, the government has established treatment guidelines and has been trying to implement training and monitoring methods. Method: This study analysed real-world data from the monitoring system implemented in the largest network of institutions receiving public funds in the State of Sao Paulo. Data came from 8109 records of individuals admitted between 2014 and 2016 in 48 institutions. Results: Results showed that less than half of the sample was exposed to at least one therapeutic activity from each of the recreational, spiritual, educational and selfcare intervention domains, as proposed by the national guidelines. Social rehabilitation outcome (SRO) defined by housing and self-support at discharge was reported by 21 % of the sample, who stayed in residential treatment for 82.6 days in average. More than half completed the therapeutic programme while 27.3 % dropout. Treatment duration and the diversity of the interventions offered were significantly associated with SRO when mutually adjusted. Chances of SRO increased nearly 5 times when residents were offered the full range of intervention domains, even when controlling for treatment duration. Treatment duration increased chances of SRO in a dose-response manner with a threefold increase for stays up to 90 days and over 9 times for stays longer than 90 days. Conclusion: Our findings offer evidence to promote treatment guidelines compliance and to pave the way for the implementation of monitoring systems for this modality of treatment in Brazil and abroad.
Keywords: Brazil; Crack cocaine; Social rehabilitation; Substance use disorder; Therapeutic community; Treatment intervention